Systematic review and meta-analysis of cardiovascular events after endovascular aneurysm repair vs open surgical repair - Catherine Boudreau, MD; Graham McClure, MD, MSc; Julien D’Astous, MD; Kamil Polok, MD, PhD; Jakub Fronczek, MD, PhD; Augustin Toma, MD; Stephen Yang, MD, MSc; Fadi Elias, MD, MSc; Wojciech Szczeklik, MD, PhD; Emmanuelle Duceppe, MD, PhD (JVS-Vascular Insights)
Objective: Randomized controlled trials (RCTs) have shown a reduction in short-term mortality with endovascular aneurysm repair (EVAR) compared with open surgical repair (OSR) but failed to demonstrate a long-term mortality advantage. Our study aims to determine whether this loss of mortality benefit could be attributed to differences in cardiovascular events. Methods: We searched MEDLINE, PubMed, Embase, and Web of Science for RCTs comparing EVAR and OSR for abdominal aortic aneurysm treatment. Title and abstracts, full texts, and study quality were assessed by two independent reviewers. Risk of bias was assessed using the Cochrane Collaboration tool for RCTs. Pooled risk ratios (RR) with 95% confidence intervals (CI) were calculated using the random-effects method, and heterogeneity was assessed using the I2 statistics. Results: Our search identified 5204 manuscripts, of which 99 full texts were screened, and 40 manuscripts included. Nine individual RCTs met the eligibility criteria. Inter-rater agreement was excellent for final study inclusion (k = 0.88). Overall, the risk of bias was low. Patients treated with EVAR had a significantly lower short-term mortality (RR: 0.65, 95% CI: 0.43-0.99). The totality of evidence on cardiovascular mortality (3 studies; 1265 patients, RR: 0.61, 95% CI: 0.16-2.25) did not rule out large differences in mortality in either direction. There were no statistically significant differences in long-term all-cause mortality (6 studies; 3436 patients, RR: 1.00, 95% CI: 0.95-1.06) and cardiovascular mortality (4 studies; 3097 patients, RR 1.09, 95% CI: 0.92-1.30), although for the later, the point estimate shifted in the other direction. Conclusions: Postoperative cardiovascular complications are frequent after abdominal aortic aneurysm repair, and most events are asymptomatic. More data are needed to inform whether the loss of mortality benefit at long-term follow-up with EVAR compared with OSR could be explained by prognostically important undetected cardiac events.